Penguasaan Puebi dan Keterkaitannya dengan Keterampilan Menulis Teks Biografi Siswa SMA - Neneng Wahyuni; Wirda Linda (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2021)
This study aims to see the correlation between PUEBI mastery and biographical text writing skills by high school students. The research method used is correlation and is classified as quantitative research. The results showed that the average PUEBI mastery of students was 88.79 with very good qualifications, and the average student biographical text writing skills were 82.79 with good qualifications (t count greater than t table, namely 17.35 > 2.042). In conclusion, there is a significant relationship between PUEBI mastery and biographical text writing skills. Keywords: PUEBI, Biographical Text